Combining Software-Implemented and Simulation-Based Fault Injection into a Single Fault Injection Method - Sieh, Volkmar; et al. (Proc. of the 25th Int. Symp. on Fault Tolerant Computing, FTCS-25, 1995)
Fault/error injection has emerged as a valuable means for evaluating the dependability of a system. In particular, software-based techniques, which can be described as software-implemented and simulation-based techniques, have become very popular because of the relative simplicity of injecting faults. After discussing the advantages and drawbacks of these techniques, two approaches are introduced which try to overcome crucial problems when using software-based fault injection techniques. The first one improves the accuracy of software-implemented fault injection experiments. The second one offers detailed insights into the system dynamics in the presence of faults. With this knowledge, the number of fault injections, a major concern in simulation-based fault injection, can be significantly reduced. These approaches can be joined together offering accuracy of fault injection results as well as transparency of the system dynamics in the presence of faults. A case study, in which the de facto dependability properties of a standard component, a Motorola MC88100 RISC processor, are evaluated shows that.
UnivIS-Import:2015-04-16:Pub.1995.tech.IMMD.IMMD3.combin